(untitled) (JBN (Jurnal Bedah Nasional), 2025)
Aim: Triple-negative breast cancer (TNBC) is associated with a highly aggressive clinical course, contributing to poorer patient outcomes and higher mortality rates. Current prognostic tools do not fully capture the complexities of the tumor immune microenvironment, particularly the role of effector lymphocytes (CD3, CD8, and CD45RO). Therefore, this study was conducted to investigate the prognostic significance of the immune markers CD3, CD8, and CD45RO within the tumor microenvironment of TNBC patients. Methods: This retrospective cohort study involved women aged >18 years old diagnosed with TNBC. Immunohistochemistry (IHC) for CD3, CD8, and CD45RO was performed using the Novolink system. Two pathologists independently assessed cell density in the tumor center (CT) and invasive margin (IM). Densities were classified as high or low using ROC curves, and the immunoscores (CD3/CD8, CD3/CD45RO) were grouped into low (I0, I1) and high (I2, I3, I4). Two-year mortality and clinical data were collected from medical records. Survival rates were analyzed using Kaplan-Meier and compared with the log-rank test. Results: The 2-year survival rate for TNBC patients was 58.3%, with a mean survival time of 18.95 months. Low CD3/CD8 was associated with significantly lower survival compared to high CD3/CD8 (42.9% vs. 73%; p=0.013), with mean survival times of 17.03 vs. 20.80 months. Similarly, low CD3/CD45RO had lower survival than high CD3/CD45RO (38.5% vs. 69.6%; p=0.01), with mean survival times of 16.37 vs. 20.43 months. Conclusion: Low CD3/CD8 and CD3/CD45RO immunoscores are associated with low survival in TNBC patients.